B Corp Movement in the Face of Challenges of Sustainable Development in the COVID-19 Pandemic. An Overview of Chosen Polish Cases - Jastrzębska, Ewa (Studia Ecologiae et Bioethicae, 2021)
The COVID-19 pandemic has led to grave and unforeseen consequences, whether in healthcare, economies, or in the lives of societies. Its multidimensional adverse impact has, according to many experts, put the achievement of the UN Sustainable Development Goals (SDGs) at risk. Nevertheless, there is a deeply held conviction that the current crisis is creating an excellent opportunity, while designing a post-pandemic reality, of avoiding the pitfalls of the previous development model. The private sector has a key role to play as it is in a position to apply various concepts of how to act responsibly and build a sustainable economy. One of such concepts is the Benefit Corporation movement. The article seeks answers to the question of whether the B Corp idea is contributing to realization of Sustainable Development Goals (SDGs), particularly those affected by the pandemic. The author offers both a theoretical (assessment of the movement and its foundations) and empirical view (analysis of chosen Polish B Corp-certified companies). This goal is to be achieved by employed research methods: a critical analysis of the literature on the subject and case studies. The author’s analyses reveal that the foundations of the B Corp movement are aligned with the sustainable development concept, and that Poland-based B Corps are contributing to the implementation of those SDGs that are particularly relevant in the time of the pandemic.